Front cover: N‐glycosylation proteomic characterization and cross‐species comparison of milk fat globule membrane proteins from mammals. Issue 21 (3rd November 2016) - Yang, Yongxin; Zheng, Nan; Wang, Weiyu; Zhao, Xiaowei; Zhang, Yangdong; Han, Rongwei; Ma, Lu; Zhao, Shengguo; Li, Songli; Guo, Tongjun; Zang, Changjiang; Wang, Jiaqi
Abstract : DOI:10.1002/pmic.201500361 Milk fat globule membrane fractions were collected from the Holstein, Jersey, buffalo, yak, goat, camel, horse, and human. N ‐linked glycosylated protein profile were identified and compared with each other among the above mentioned mammals. Identified N ‐linked glycosylated proteins from these mammals were shown to be associated with response to stimulus. For more details, see the article by Yongxin Yang et al. on page 2792.